Yellow metal interference pigment with light green, method for preparing same and use thereof
By coating the silicon dioxide and iron oxide (III) layers of specific structures on the aluminum sheet, the problem that existing metal interference pigments cannot meet the light green yellow tone and high color saturation is solved, and efficient hue and saturation control is achieved .
Patent Information
- Application Number
- CN202380054893.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-06-29
- Publication Date
- 2025-02-21
AI Technical Summary
The metal interference pigments on the existing market cannot meet the requirements of yellow tone with light green tint and high color saturation.
The mole fraction and layer of the dopant element of layer B of layer B are adjusted by sequentially coating the silica layer A and iron (III) oxide layer B doped with tungsten, indium, gallium and titanium dopant elements on the aluminum sheet. Thickness to achieve the desired hue and saturation.
The metal interference pigment has a hue angle hab15° of at least 85 and a hue Cab15° of at least 55, ie, a yellow tone with a light green and high color saturation.
Smart Images

Figure SMS_22
Abstract
Description
[0001] The present invention relates to a yellow metallic interference pigment with a light green color, a method for preparing the metallic interference pigment and use thereof.
[0002] In recent years, metallic interference pigments have been established for coloring paints, printing inks, inks, plastics, glass, ceramics and decorative cosmetic preparations. The characteristic of metallic interference pigments is that a metal substrate (for example made of aluminum, which can be stabilized with a silicon dioxide layer on top) is surrounded by a highly refractive metal oxide layer (such as an iron (III) oxide layer). Since the metal substrate is opaque, the metallic interference pigments have a high hiding power compared to pearlescent pigments comprising a translucent substrate.
[0003] When light is incident on the metallic interference pigment, a part of the incident light penetrates the high refractive index metal oxide layer, and another part of the incident light is reflected at the surface of the high refractive index metal oxide layer. The part of the incident light that penetrates the high refractive index metal oxide layer is finally reflected at the surface of the metal substrate. The light reflected at the surface of the metal substrate and the light reflected at the surface of the high refractive index metal oxide layer show path differences, which produces the interference phenomenon that eventually causes the metallic interference pigment to be colored. The selection of the suitable high refractive index metal oxide layer can be used to set the required color tone, and the refractive index and layer thickness also have an impact on the color tone.
[0004] For various applications, it is desirable to use metallic interference pigments having a yellow tone with a green tint, corresponding to a hue angle h of at least 85. ab At the same time, it is desirable that the metallic interference pigment has a high color saturation, equivalent to a hue (chroma) C of at least 55. ab 15°.
[0005] The metallic interference pigments currently available on the market do not meet the above requirements.
[0006] For example, Zenexo from Schlenk Metallic Pigments GmbH ® GoldenShine, Meoxal from Merck KGaA ® Taklamakan Gold and Paliocrom from Sun Chemical Colors & Effects GmbH ® The metallic interference pigment of Gold only shows a yellow hue, without a light green. In this article, reference is also made to the metallic interference pigment disclosed in WO2019 / 063372 A1, whose hue angle is only in the range of 68 to 78, which is not yet a greenish yellow.
[0007] The present invention is therefore based on the object of providing yellow metallic interference pigments with a greenish hue, which metallic interference pigments should also have a high color saturation.
[0008] The above object is achieved by providing a metallic interference pigment according to the invention comprising aluminum platelets having an average thickness of 5 nm to 600 nm, the aluminum platelets being optionally passivated and coated in sequence with a layer A and a layer B,
[0009] wherein the layer A consists of silicon dioxide and the layer B consists of iron(III) oxide doped with a dopant element selected from the group consisting of tungsten, indium, gallium and titanium,
[0010] wherein the molar fraction of the dopant element in the layer B is 0.5 mol % to 10 mol % based on the total molar amount of iron and the dopant element, and
[0011] The metallic interference pigment contains 60 to 85 parts by mass of iron (III) oxide, based on 10 parts by mass of aluminum.
[0012] The metallic interference pigments according to the invention which can be obtained by the manufacturing method according to the invention described below are characterized by having a greenish yellow chromaticity. This is achieved by doping the high-refractive metal oxide layer with small amounts of specific dopant elements other than iron(III) oxide. Doping allows the hue angle of the metallic interference pigment to be shifted towards higher values without having to accept a loss in hue.
[0013] The metallic interference pigments according to the invention are described in more detail below.
[0014] As already mentioned above, the metallic interference pigments according to the present invention comprise aluminium flakes. The aluminium flakes used as metal substrates can be passivated, i.e. they can be coated with a natural oxide layer. The thickness of the natural oxide layer is typically 3 nm to 5 nm and, as indicated below, is included in the thickness of the aluminium flakes in the context of the present invention.
[0015] According to the invention, the aluminum flakes have an average thickness of 5 nm to 600 nm, preferably 5 nm to 400 nm, more preferably 5 nm to 200 nm, even more preferably 5 nm to 100 nm, for example 10 nm to 50 nm or 15 nm to 30 nm. By using thin aluminum flakes, particularly high hiding power can be achieved, because a larger area of the surface to be covered by the metallic interference pigment can be covered by the same mass of aluminum. The average thickness of the aluminum flakes is their average thickness, which is understood to be the arithmetic mean of all measured thicknesses. The average thickness of the aluminum flakes is determined by measurements based on scanning transmission electron microscopy (STEM) images. The average thickness of the aluminum flakes is the average of at least 200 measurements of different aluminum flakes.
[0016] The invention is not further limited as far as the size of the aluminium flakes, ie their diameter, is concerned. The diameter of the aluminium flakes in this application is the so-called d 50 This means that 50% of the aluminum sheets from the random sample have values less than the specified value. Without limitation, the diameter d of the aluminum sheet 50 Typically 5 μm to 100 μm, for example 5 μm to 50 μm or 10 μm to 30 μm. The diameter d of the aluminum flakes is determined by laser diffraction-based measurement according to DIN ISO 13320:2020-01 using a commercially available particle size analyzer, for example a particle size analyzer commercially available from Sympatec GmbH (Helios BF with Quixel wet dispersion, lens 3). 50 .
[0017] Diameter of aluminum sheet d 50 The ratio between the average thickness of the aluminum sheet (also referred to as the aspect ratio) is not subject to any particular restrictions in the present application. It can be 50 to 5000, 100 to 2000 or 200 to 1000, but is not limited thereto.
[0018] Ideally, the aluminum sheet has a thickness SPAN (t SPAN ), but not limited thereto. The thickness SPAN is derived from the width of the thickness distribution and is calculated according to the following formula:
[0019]
[0020] With diameter d 50 Similarly, the indicators in the above formula represent the corresponding values in the cumulative distribution curve. Therefore, t 10 It means that 10% of the aluminum sheet has a thickness of t 10 Thinner. Accordingly, 90% of the aluminum sheets have a thickness equal to or greater than t 10 Similar considerations apply to the thickness t 50 and thickness t90 .
[0021] Finally, the thickness variation (Δh) is obtained as a percentage of the thickness SPAN:
[0022]
[0023] Therefore, a thickness SPAN of 0.1 to 0.4 means that the thickness variation is 10% to 40%.
[0024] Aluminum flakes may be those resulting from wet grinding. Aluminum flakes obtained by wet grinding are also called "corn flakes" or "silver dollar" according to their appearance. While aluminum flakes of the "corn flake" type (also called lamellar type) have irregular and jagged sides, aluminum flakes of the "silver dollar" type (also called lens type) generally have rounded edges.
[0025] Aluminum flakes can also be obtained by replacing wet grinding with physical vapor deposition (PVD). The aluminum flakes obtained in this way are also called vacuum metallized pigments (VMP). According to their appearance, they are polygons with straight sides. Due to their manufacturing method, vacuum metallized pigments have extremely low thickness variation and are also significantly smoother than aluminum flakes from wet grinding. Metal interference pigments based on vacuum metallized pigments not only have excellent color saturation, but are also excellent in their hiding power. Therefore, preferably, the aluminum flakes of the metal interference pigments according to the present invention are vacuum metallized pigments. Vacuum metallized pigments are commercially available from various suppliers. In this article, for example, vacuum metallized pigments Decomet from Schlenk MetallicPigments GmbH should be mentioned. ® , METALURE from Eckart GmbH ® and Metasheen from SunChemical Colors & Effects GmbH ® .
[0026] According to the invention, the aluminum sheet is coated sequentially with layer A and layer B. Thus, first layer A is applied to the aluminum sheet. Then layer B is applied to this layer. Thus, layers A and B envelop the aluminum sheet, with layer A being arranged between the aluminum sheet and layer B. Typically, the aluminum sheet is coated with layers A and B in such a way that the coating is complete in each case.
[0027] Layer A, which is made of silicon dioxide and has a low refractive index (refractive index n ≤ 1.8), serves to stabilize the aluminum flakes. Layer A thus protects the aluminum flakes from direct exposure to the conditions prevailing during the subsequent formation of layer B.
[0028] Without being limited thereto, layer A may have an average thickness of 5 nm to 200 nm, for example, 10 nm to 100 nm. For the determination of the average thickness of layer A, the same explanation as above regarding the determination of the average thickness of the aluminum sheet applies, except that only 100 samples are measured and evaluated by scanning electron microscope (SEM) images.
[0029] The high refractive index (refractive index n> 1.8) of layer B is the main cause of interference and therefore the cause of the coloring of the metallic interference pigments. In the present application, layer B consists of iron (III) oxide doped with a dopant element selected from tungsten, indium, gallium and titanium. The presence of the dopant element in layer B affects the refractive index of layer B, so that the hue angle of the metallic interference pigment is shifted to a larger value, as a result of which the metallic interference pigment finally has a greenish yellow color. Preferably, the dopant element is tungsten, because this is easily obtained in the form of corresponding compounds.
[0030] As for the amount of dopant elements, the molar fraction of the dopant elements in layer B is 0.5 mol% to 10 mol%, preferably 1.0 mol% to 8 mol%, and even more preferably 1.5 mol% to 7 mol%, based on the total molar amount of iron and dopant elements. If the amount of dopant elements is too small, a yellow color with a light green color is not yet achieved. If the amount of dopant elements is too high, the color saturation is reduced, which is evident in the reduction of the hue of the metallic interference pigment. The molar fraction of the dopant elements in layer B relative to the total molar amount of iron and doping elements is determined using an energy dispersive X-ray spectrometer (EDX).
[0031] As already mentioned at the outset, in addition to the refractive index, the thickness of layer B also influences the color tone. Typically, layer B has an average thickness of 15 nm to 300 nm, whereby the average thickness of layer B may be, for example, 25 nm to 200 nm or 50 nm to 150 nm. For the determination of the average thickness of layer B, the same applies as explained above with regard to the determination of the average thickness of the aluminum sheet, with the difference that only 100 samples are measured and evaluated by scanning electron microscope (SEM) images.
[0032] In both the case of layer A and the case of layer B, the thickness of the respective layers can be adjusted by the amount of the respective precursor compounds added. In the case of providing the same amount of aluminum flakes, the more respective precursor compounds are added, the thickness of the respective layers increases. Therefore, the amount of the precursor compounds added is adjusted in such a way that layer A and layer B have suitable thicknesses (e.g., within the above range). The precursor compounds of layer A and layer B will be discussed in more detail below in the description of the manufacturing method according to the present invention.
[0033] According to the invention, based on 10 parts by mass of aluminum, there are 60 to 85 parts by mass, for example 60 to 80 parts by mass or 60 to 75 parts by mass of iron(III) oxide in the metallic interference pigment. The person skilled in the art knows that if the aluminum flakes become thinner, the mass of iron(III) oxide must be increased to achieve a certain layer thickness, provided that the mass of aluminum remains constant. The reason for this is that as the aluminum flakes become thinner, their surface area to be coated increases. The above considerations of course apply not only to layer B, but also to layer A in the same way.
[0034] Layer B may be provided with a surface coating as layer C. Without limitation, the surface coating may be formed, for example, from an organic polymer, a silane or a siloxane. The surface coating may also consist of silicon dioxide, as described below in conjunction with the production method according to the invention. In principle, a combination of silicon dioxide and silanes, etc. is also possible.
[0035] The mechanical and chemical resistance of the metallic interference pigments can be further increased by applying such a surface coating to layer B, which is also referred to as surface functionalization. However, such a surface coating is not absolutely necessary. Therefore, the metallic interference pigments can also consist of aluminum flakes with an average thickness of 5 nm to 600 nm, which can be passivated and coated with layers A and B in sequence. Therefore, in addition to layers A and B, there are no further layers on the optionally passivated aluminum flakes in this embodiment.
[0036] Due to their specific structure, as described above, the metallic interference pigments according to the invention have both a greenish yellow hue and a high color saturation. In other words, the metallic interference pigments according to the invention have a hue angle h of at least 85. ab 15° and a hue of at least 55 C ab 15°.
[0037] In order to determine the color characteristics, namely the hue angle h ab 15° and Hue C ab15 °, first prepare a coating formulation consisting of 0.7 g of metallic interference pigment and 9.3 g of a coating containing butanol wet nitrocellulose and polycyclohexanone resin and another resin based on butyl acrylate-isobutyl vinyl ether (8.5% by mass solids content). Therefore, the pigmentation is 7% by mass. After mixing the coating formulation using a fast mixer from Hauschild & Co KG to disperse the metallic interference pigment in the coating formulation, it is applied to black and white test paperboard (DIN A5 with optical brightener) from TQC Sheen GmbH using a film applicator from Zehntner GmbH and a 38 μm doctor blade from TQC Sheen GmbH. After the blade coating, subsequent drying is carried out, first at room temperature, i.e. at 25° C. and then at 60° C., and then the spectral reflection of the light beam incident on the measurement surface at an angle of 45° and emitted by the D65 light source is measured at six different detection angles (15°, 15°, 25°, 45°, 75° and 110°) for a 10° observer using a commercially available multi-angle spectrophotometer in accordance with DIN EN ISO 18314-3:2018-12 and converted into the corresponding values in the CIELAB color space. Here, the measurements are carried out with a "BYK-mac i" multi-angle spectrophotometer from BYK-Gardner GmbH on a "Color Scout A+" vacuum measuring table from ColorPartner GmbH. This is also used to determine the color distances as described below E110°.
[0038] In addition to their coloristic properties, the metallic interference pigments according to the invention can also be characterized by their color distance ΔE110°. E110° is a measure of the hiding power of metallic interference pigments, whereby the smaller the color distance E110° means higher hiding power. At E110°, as described above, a doctor blade coating is first required, so that the pigmentation here is also 7% by mass. The color distance is then measured according to DIN 6175:2019-07 with a commercially available multi-angle spectrophotometer in a geometry of 45° / 110°.
[0039] Since the aluminum flakes used as metal substrate are opaque, the metallic interference pigments according to the invention generally have a color distance ΔE110° of less than 1.5. This applies all the more if thin aluminum flakes are used, for example those with an average thickness of 5 nm to 30 nm, and / or if vacuum metallized pigments are used for this purpose.
[0040] Furthermore, the present invention provides a method for producing the metallic interference pigments according to the present invention as described above, wherein the production method according to the present invention comprises the following steps (a) to (c):
[0041] (a) providing an aluminum flake having an average thickness of 5 nm to 600 nm, the aluminum flake being optionally passivated;
[0042] (b) coating the aluminum sheet provided in step (a) with a layer A of silicon dioxide by hydrolytic decomposition of an organosilicon compound or by precipitation of water glass; and
[0043] (c) coating the layer A obtained in step (b) with a layer B of iron(III) oxide doped with a dopant element selected from tungsten, indium, gallium and titanium by precipitating an iron salt in the presence of a dopant salt selected from tungsten salts, indium salts, gallium salts and titanium salts.
[0044] The metallic interference pigment obtainable by the production method according to the invention has a greenish yellow color and a high color saturation.
[0045] The production process according to the invention is described in more detail below, the definitions made here in relation to the metallic interference pigments according to the invention also applying unless otherwise stated below.
[0046] In step (a) of the manufacturing method according to the invention, an aluminum flake having an average thickness of 5 nm to 600 nm is provided, which is optionally passivated. For this purpose, the aluminum flake can be provided in a suspended form. An organic solvent can be used to suspend the aluminum flake, such as isopropanol, which is also particularly suitable for the coating process in the subsequent step (b).
[0047] In step (b) of the manufacturing method according to the invention, the aluminum sheet provided in step (a) is coated with a layer A of silicon dioxide. This can be done by hydrolytic decomposition of an organosilicon compound. An example of an organosilicon compound is tetraethyl orthosilicate (TEOS), which is also known as tetraethoxysilane. However, in principle, any other organosilicon compound can also be used, provided that it has a hydrolyzable group. Alternatively, the coating in step (b) can be carried out by precipitation of water glass.
[0048] For the coating in step (b), the hydrolytic decomposition is preferably carried out in the presence of a base or an acid as a catalyst. Suitable alkaline catalysts include alkaline solutions, such as sodium hydroxide solution or potassium hydroxide solution, in particular aqueous ammonia solution. Suitable acidic catalysts include phosphoric acid and carboxylic acids, such as acetic acid and oxalic acid. For the hydrolytic decomposition, water must be present in an amount at least required for stoichiometry, whereby an excess of water is usually used. For temperature control, the reaction mixture is preferably gradually heated to 70° C. to 75° C. over a period of 10 to 48 hours.
[0049] If the coating in step (b) is carried out by precipitation of water glass, a sodium silicate (DAB6) solution is usually added at 70° C. over 2 hours. Depending on the size of the reactor and the pigment surface, the dosing is carried out at a rate of 0.1 l / min to 0.2 l / min, whereby the pH value is kept constant at 8.0 with dilute sulfuric acid. Stirring is then continued for 15 minutes, during which the pH value hardly changes.
[0050] After the hydrolytic decomposition of the organosilicon compound or the precipitation of water glass, the aluminum sheet coated with layer A is separated from the other components of the reaction mixture using a filter press and washed. Further details about the coating process in step (b) are known to those skilled in the art and can be found, for example, in WO 2015 / 014484 A1.
[0051] In step (c) of the manufacturing method according to the present invention, the layer A obtained in step (b) is coated with a layer B of iron (III) oxide, and the iron (III) oxide is doped with a dopant element selected from tungsten, indium, gallium and titanium. This is done by precipitating an iron salt in the presence of a dopant salt selected from tungsten salts, indium salts, gallium salts and titanium salts. The iron salt is usually iron (III) chloride, although other iron salts can also be used, provided that they can eventually be precipitated into iron (III) oxide. Not limited to this, the dopant salt can be selected from sodium tungstate (dihydrate), indium (III) chloride, gallium (III) nitrate and titanium (IV) oxychloride (x hydrogen chloride). In particular, sodium tungstate (dihydrate) has been shown to be advantageous for doping due to its easy availability. However, in principle, dopant salts other than those mentioned above are also conceivable, as long as they can be used to appropriately dope.
[0052] For the coating in step (c), the aluminum sheet of layer A coated with silicon dioxide from step (b) can be used immediately, which exists as an aqueous slurry after washing. Therefore, no resuspension is required. The pH value is then adjusted to about 3.4 by adding acid. Then an aqueous solution of an iron salt is added. At the same time, an ammonia solution or the like is added. This induces precipitation and keeps the pH constant at the same time, otherwise the pH will be reduced due to the precipitation reaction, such as when using iron (III) chloride, due to the release of hydrogen chloride, this will occur. The dopant salt can be present in an aqueous solution of an iron salt, such as in the case of indium (III) chloride, gallium (III) nitrate and titanium (IV) oxychloride (x hydrogen chloride), or in an ammonia solution, such as in the case of sodium tungstate (dihydrate). The amount of the iron salt is selected so that based on 10 parts by mass of aluminum, there are 60 to 85 parts by mass of iron (III) oxide in the metal interference pigment. The amount of the dopant salt is selected so that the molar fraction of the dopant element in layer B is 0.5 mol% to 10 mol% based on the total molar amount of iron and dopant elements. This ensures that the metallic interference pigments have a greenish yellow hue, corresponding to a hue angle h of at least 85. ab 15°, with high color saturation, equivalent to a hue of at least 55 C ab 15°.
[0053] Typically, the iron salt used is converted quantitatively during the coating process in step (b). The same applies to the dopant salt.
[0054] After precipitation of the iron salt in the presence of the dopant salt, the pH is adjusted to about 5. After cooling and washing the aluminum sheets coated with layers A and B, they are dried in vacuo at a temperature of 60° C. The aluminum sheets coated with layers A and B are then subjected to a heat treatment characterized by being kept at a temperature of 250° C. to 400° C. for a period of 30 minutes to 2 hours. This converts the initially formed iron(III) hydroxide doped with a dopant element selected from tungsten, indium, gallium and titanium into the corresponding iron(III) oxide. Further details about the precipitation in step (c) are known to the person skilled in the art and can be found, for example, in WO 2015 / 014484 A1.
[0055] The metallic interference pigments obtained in step (c) can now be used immediately. If desired, in the subsequent step (d), layer B can be provided with a surface coating, which is formed, for example, from organic polymers, silanes or siloxanes. The process in this regard is described in detail in WO 2015 / 044188 A1, among others. If the surface coating consists of silicon dioxide, the method can be carried out as in step (b).
[0056] Finally, the present invention provides the use of the metallic interference pigments according to the invention for coloring paints, printing inks, inks, plastics, glass, ceramics and decorative cosmetic preparations. By coloring with the metallic interference pigments according to the invention, the corresponding products are simultaneously given a greenish yellow hue and a high color saturation. This is not possible with the metallic interference pigments known from the prior art.
[0057] Example
[0058] The following examples are provided to further illustrate the present invention, but are not intended to limit the present invention.
[0059] In each of the following examples and comparative examples, 600 g of an aqueous suspension of passivated aluminum flakes coated with an approximately 40 nm thick silicon dioxide layer were used. Commercially available aluminum flakes (Decomet from Schlenk Metallic Pigments GmbH) ® ) has an average thickness of about 25 nm and a diameter d of about 12 μm 50 The solids content of the aqueous suspension is 7.5% by mass. The aqueous suspension thus contains 45 g of passivated aluminum flakes coated with a silicon dioxide layer, of which about 15 g are made up of aluminum flakes.
[0060] SiO2 layer is formed on the aluminum sheet of passivation as follows: 153.5 g suspension of vacuum metallized pigment (solid content is 14.6 quality %) in isopropanol is placed in a container, diluted with 100.5 g ethanol and heated to a temperature of 70 ℃. Then add 3.5 g 10% potassium hydroxide solution in ethanol. At a temperature of 70 ℃, add a mixture of 53.4 g TEOS and 170 g water and 10.9 g 25% ammonia aqueous solution successively. After 30 minutes reaction time, carry out the second addition of TEOS (46.6 g), after another 30 minutes reaction time, carry out the third addition of TEOS (41.3 g), and after another 30 minutes reaction time, carry out the fourth addition of TEOS (17.0 g), carry out the final reaction time of 1 hour subsequently. Subsequently, add 300 g water, and the mixture is transferred in a larger container. Then by adding 2200 g water further dilute the mixture while stirring. Subsequently, 0.5 g of citric acid was added, followed by sedimentation for a period of 12 to 24 hours. The supernatant was removed and water was added again. After a period of re-sedimentation for 12 to 24 hours, the supernatant was removed again. Finally, water was added until an aqueous suspension having a solid content of 7.5% by weight as described above was obtained.
[0061] Example A
[0062] After the aqueous suspension is heated to a temperature of about 75 ° C and the pH is adjusted to about 3.4, 518.0 g of a 40% solution of iron (III) chloride in water is added. At the same time, 365.8 g of an 18.25% ammonia solution is added to induce precipitation and keep the pH constant. Sodium tungstate (dihydrate) is used as a dopant salt, which is added to the ammonia solution in advance. The dopant salt accounts for 8.2 g of the ammonia solution, which is equivalent to a mass fraction of sodium tungstate (dihydrate) in the ammonia solution of about 2.25 mass%. The coating of layer B is carried out in a manner that 68.0 g of iron (III) oxide is present in the metallic interference pigment based on 10 g of aluminum. For this purpose, the aluminum sheet used is considered to be first subjected to appropriate preliminary tests.
[0063] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0064] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above. ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0065] Example B
[0066] After the aqueous suspension is heated to a temperature of about 75 ° C and the pH is adjusted to about 3.4, 540.8 g of a 40% solution of iron (III) chloride in water is added. At the same time, 382.0 g of an 18.25% ammonia solution is added to induce precipitation and keep the pH constant. Sodium tungstate (dihydrate) is used as a dopant salt, which is added to the ammonia solution in advance. The dopant salt accounts for 8.6 g of the ammonia solution, which is equivalent to a mass fraction of sodium tungstate (dihydrate) in the ammonia solution of about 2.25 mass%. The coating of layer B is carried out in a manner that the metal interference pigment contains 71.0 g of iron (III) oxide based on 10 g of aluminum. For this purpose, the aluminum sheet used is considered to be first subjected to appropriate preliminary tests.
[0067] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0068] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above. ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0069] Example C
[0070] After the aqueous suspension is heated to a temperature of about 75 ° C and the pH is adjusted to about 3.4, 492.8 g of a 40% solution of iron (III) chloride in water is added. At the same time, 364.9 g of an 18.25% ammonia solution is added to induce precipitation and keep the pH constant. Sodium tungstate (dihydrate) is used as a dopant salt, which is previously added to the ammonia solution. The dopant salt accounts for 24.7 g of the ammonia solution, which is equivalent to a mass fraction of sodium tungstate (dihydrate) in the ammonia solution of about 6.76% by mass. Layer B is applied in such a way that the metallic interference pigment contains 64.7 g of iron (III) oxide based on 10 g of aluminum. For this purpose, the aluminum sheets used are first subjected to appropriate preliminary tests.
[0071] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0072] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above. ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0073] Example D
[0074] After the aqueous suspension is heated to a temperature of about 75 ° C and the pH is adjusted to about 3.4, 519.5 g of a 40% solution of iron (III) chloride in water is added. At the same time, 384.7 g of an 18.25% ammonia solution are added to induce precipitation and keep the pH constant. Sodium tungstate (dihydrate) is used as a dopant salt, which is previously added to the ammonia solution. The dopant salt accounts for 26.0 g of the ammonia solution, which is equivalent to a mass fraction of sodium tungstate (dihydrate) in the ammonia solution of about 6.76% by mass. The coating of layer B is carried out in a manner that 68.2 g of iron (III) oxide is present in the metallic interference pigment based on 10 g of aluminum. For this purpose, the aluminum sheets used are first subjected to appropriate preliminary tests.
[0075] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0076] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above. ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0077] Example E
[0078] After heating the aqueous suspension to a temperature of about 75 ° C and adjusting the pH to about 3.4, 537.0 g of a 40% solution of iron (III) chloride in water are added. At the same time, 397.6 g of an 18.25% ammonia solution are added to induce precipitation and keep the pH constant. Sodium tungstate (dihydrate) is used as a dopant salt, which is previously added to the ammonia solution. The dopant salt accounts for 26.9 g of the ammonia solution, which is equivalent to a mass fraction of sodium tungstate (dihydrate) in the ammonia solution of about 6.76% by mass. The coating of layer B is carried out in a manner that 70.5 g of iron (III) oxide is present in the metallic interference pigment based on 10 g of aluminum. For this purpose, the aluminum sheets used are first subjected to appropriate preliminary tests.
[0079] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0080] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above. ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0081] Example F
[0082] After heating the aqueous suspension to a temperature of about 75° C. and adjusting the pH to about 3.4, 542.1 g of a 40% solution of iron (III) chloride in water are added. At the same time, 368.1 g of an 18.25% aqueous ammonia solution are added to induce precipitation and keep the pH constant. Indium (III) chloride is used as a dopant salt, which is previously added to the aqueous solution of iron (III) chloride. The dopant salt accounts for 8.9 g of the aqueous solution of iron (III) chloride, which corresponds to a mass fraction of indium (III) chloride in the aqueous solution of iron (III) chloride of about 1.65% by mass. The coating of layer B is carried out in such a way that 70.0 g of iron (III) oxide are present in the metallic interference pigment based on 10 g of aluminum. For this purpose, the aluminum sheets used are first subjected to appropriate preliminary tests.
[0083] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0084] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above. ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0085] Example G
[0086] After heating the aqueous suspension to a temperature of about 75° C. and adjusting the pH to about 3.4, 493.1 g of a 40% solution of iron(III) chloride in water are added. At the same time, 333.9 g of an 18.25% aqueous ammonia solution are added to induce precipitation and keep the pH constant. Gallium(III) nitrate is used as a dopant salt, which is previously added to the aqueous solution of iron(III) chloride. The dopant salt accounts for 9.4 g of the aqueous solution of iron(III) chloride, which corresponds to a mass fraction of gallium(III) nitrate in the aqueous solution of iron(III) chloride of about 1.91% by mass. Layer B is applied in such a way that 63.5 g of iron(III) oxide are present in the metallic interference pigment based on 10 g of aluminum. For this purpose, the aluminum sheets used are first subjected to appropriate preliminary tests.
[0087] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0088] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above. ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0089] Example H
[0090] After heating the aqueous suspension to a temperature of about 75° C. and adjusting the pH to about 3.4, 548.3 g of a 40% solution of iron (III) chloride in water are added. At the same time, 371.3 g of an 18.25% aqueous ammonia solution are added to induce precipitation and keep the pH constant. Gallium (III) nitrate is used as a dopant salt, which is previously added to the aqueous solution of iron (III) chloride. The dopant salt accounts for 10.5 g of the aqueous solution of iron (III) chloride, which corresponds to a mass fraction of gallium (III) nitrate in the aqueous solution of iron (III) chloride of about 1.91% by mass. The coating of layer B is carried out in such a way that 70.6 g of iron (III) oxide are present in the metallic interference pigment based on 10 g of aluminum. For this purpose, the aluminum sheets used are first subjected to appropriate preliminary tests.
[0091] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0092] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above. ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0093] Embodiment 1
[0094] After the water suspension is heated to a temperature of about 75 ° C and the pH is adjusted to about 3.4, 569.4 g of 40% solution in iron chloride (III) water is added. At the same time, 356.6 g of 18.25% ammonia solution is added to induce precipitation and keep pH constant. Titanium (IV) oxychloride (x hydrogen chloride) is used as a dopant salt, which is added to the iron chloride (III) aqueous solution in advance. The dopant salt accounts for 53.0 g of the iron chloride (III) aqueous solution, which is equivalent to about 9.30 mass % of the mass fraction of titanium (IV) oxychloride (x hydrogen chloride) in the iron chloride (III) aqueous solution. The coating of layer B is carried out in a manner in which 67.8 g of iron oxide (III) is present in the metal interference pigment based on 10 g of aluminum. For this purpose, it is considered that the aluminum sheet used is first subjected to appropriate preliminary tests.
[0095] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0096] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above. ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0097] Comparative Example A
[0098] After heating the aqueous suspension to a temperature of about 75° C. and adjusting the pH to about 3.4, 490.6 g of a 40% solution of iron(III) chloride in water were added. At the same time, 338.7 g of an 18.25% aqueous ammonia solution were added to induce precipitation and to keep the pH constant. Layer B was applied in such a way that the metallic interference pigment contained 64.4 g of iron(III) oxide based on 10 g of aluminum. For this purpose, the aluminum sheets used were first subjected to appropriate preliminary tests.
[0099] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0100] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above.ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0101] Comparative Example B
[0102] After heating the aqueous suspension to a temperature of about 75° C. and adjusting the pH to about 3.4, 518.7 g of a 40% solution of iron(III) chloride in water were added. At the same time, 358.1 g of an 18.25% aqueous ammonia solution were added to induce precipitation and to keep the pH constant. The coating of layer B was carried out in such a way that 68.1 g of iron(III) oxide were present in the metallic interference pigment based on 10 g of aluminum. For this purpose, appropriate preliminary tests were first carried out taking into account the aluminum sheets used.
[0103] The pH value was then adjusted to about 5. After cooling and washing, vacuum drying was carried out at a temperature of about 60° C. Finally, the solid obtained in this way was subjected to a heat treatment, whereby it was first heated from room temperature to 270° C. at a heating rate of 1.5° C. / min, then from 270° C. to 370° C. at a heating rate of 0.5° C. / min, and subsequently kept at 370° C. for 1 hour.
[0104] After the heat treatment, the color properties of the resulting metallic interference pigments were examined, namely the hue angle h as described above. ab 15° and Hue C ab 15°. The results are shown in Table 1.
[0105] Table 1
[0106]
[0107] It can be seen from the above examples A to I that by doping with a dopant element selected from tungsten, indium, gallium and titanium, a hue angle h of at least 85 can be achieved. ab 15° and a hue of at least 55 C ab 15°. Thus, the metallic interference pigments from Examples A to I are characterized by a greenish yellow hue and a high color saturation. In contrast, without doping, only hue angles h below 80° can be achieved. ab 15°, as can be seen from the above Comparative Examples A and B. Therefore, the metallic interference pigments from Comparative Examples A and B do not exhibit a yellow hue with a greenish color.
Claims
1. Metallic interference pigments comprising aluminum flakes having an average thickness of 5 nm to 600 nm, which are optionally passivated and coated in sequence with a layer A and a layer B, wherein the layer A consists of silicon dioxide and the layer B consists of iron(III) oxide doped with a dopant element selected from the group consisting of tungsten, indium, gallium and titanium, wherein the molar fraction of the dopant element in the layer B is 0.5 mol % to 10 mol % based on the total molar amount of iron and the dopant element, and The metallic interference pigment contains 60 to 85 parts by mass of iron (III) oxide, based on 10 parts by mass of aluminum.
2. The metallic interference pigment according to claim 1, wherein the diameter d of the aluminum flakes is 50 It is 5 μm to 100 μm.
3. The metallic interference pigment according to claim 1 or 2, wherein the aluminum flakes have a thickness variation of 10% to 40%.
4. The metallic interference pigment according to any one of claims 1 to 3, wherein the aluminum flakes are vacuum metallized pigments.
5. The metallic interference pigment according to any one of claims 1 to 4, wherein the layer A has an average thickness of 5 nm to 200 nm.
6. The metallic interference pigment according to any one of claims 1 to 5, wherein the dopant element is tungsten.
7. The metallic interference pigment according to any one of claims 1 to 6, wherein the layer B has an average thickness of 15 nm to 300 nm.
8. The metallic interference pigment according to any one of claims 1 to 7, wherein the layer B is provided with a surface coating.
9. The metallic interference pigment according to any one of claims 1 to 8, wherein the metallic interference pigment has a hue C of at least 55. ab At 15°, the hue angle h is at least 85 ab 15°. 10 . The metallic interference pigment according to claim 1 , wherein the metallic interference pigment has a color distance ΔE110° of less than 1.
5.
11. A method for producing a metallic interference pigment according to any one of claims 1 to 10, comprising the following steps (a) to (c): (a) providing an aluminum flake having an average thickness of 5 nm to 600 nm, the aluminum flake being optionally passivated; (b) coating the aluminum sheet provided in step (a) with a layer A of silicon dioxide by hydrolytic decomposition of an organosilicon compound or by precipitation of water glass; and (c) coating said layer A obtained in step (b) with a layer B of iron(III) oxide doped with a dopant element selected from tungsten, indium, gallium and titanium by precipitating an iron salt in the presence of a dopant salt selected from tungsten salts, indium salts, gallium salts and titanium salts.
12. The method of claim 11, wherein the dopant salt is selected from the group consisting of sodium tungstate (dihydrate), indium (III) chloride, gallium (III) nitrate, and titanium (IV) oxychloride (x-hydrogen chloride).
13. The method of claim 12, wherein the dopant salt is sodium tungstate (dihydrate).
14. The method according to any one of claims 11 to 13, further comprising the following step (d): (d) providing said layer B obtained in step (c) with a surface coating.
15. Use of the metallic interference pigments according to any one of claims 1 to 10 for coloring paints, printing inks, inks, plastics, glass, ceramics and decorative cosmetic preparations.
Citation Information
Patent Citations
Metallic lustre pigments based on substrate flakes with a thickness of 1-50 nm
WO2015014484A1
Metal effect pigments modified with a silane layer containing at least two different bifunctional silanes
WO2015044188A1
Golden effect pigments with a hue (H15) in the range of 67° 78° and a chroma (c*15) of more or equal than 90
WO2019063372A1